Integrating wood fuels into agriculture and food security agendas and research in sub-Saharan Africa - Mendum, R.; Njenga, M. (Canadian Science Publishing, 2018)
In sub-Saharan Africa (SSA), food security can be influenced by many factors including farmer productivity, access to soil amendments, labor availability, and family incomes (just to name a few). In this paper, we suggest that an additional issue contributes to food insecurity and has been historically absent from the discussion, namely access to cooking energy, particularly for very low income, food insecure individuals. This paper examines the most recent literature that describes the central role played by wood fuels, in particular firewood and charcoal, as a vital, though controversial, source of fuel used by the vast majority of rural and urban sub-Saharan Africans. We explore the reality that although the health risks of collecting and using firewood and charcoal in traditional manners are real, policy makers, researchers, and donors need to address the sustainability and viability of the current fuel types used by the majority of people. We end the paper with a series of practical suggestions for improving the wood fuel systems as they currently exist in the region.